A) m = 2017b) m = 2018²c) m = 2018d) m = e) m = 2019

A) m = 2017
b) m = 2018²
c) m = 2018
d) m =

e) m = 2019


A) m = 2017b) m = 2018²c) m = 2018d) m = e) m = 2019

1 Resposta

Kauany

frac{ {x}^{5} - {x}^{3} }{ {x}^{4} - {x}^{3} } = frac{ {x}^{3}( {x}^{2} - 1) }{ {x}^{3} (x - 1)} = frac{ {x}^{2} - 1}{x - 1} = \ frac{(x + 1)(x - 1)}{(x - 1)} = x + 1 = 2018 + 1 = \ = oxed{2019}

RESPOSTA:Letra E​

Mais perguntas de Matemática





















Toda Materia
Toda Materia
Toda Materia

Você tem alguma dúvida?

Faça sua pergunta e receba a resposta de outros estudantes.